MESIN PENDINGIN PORTABEL BAGI KELOMPOK PENJUAL IKAN KELILING DI KELURAHAN TUMAMPUA, KABUPATEN PANGKEP - Iwan Suhardi; Edi Suhardi Rahman; Massikki; Alifya NFH (Jurusan Teknik Informatika dan Komputer, 2023)
Community Partnership Program Partners (PKM) are a group of mobile fish sellers selling fresh fish around Pangkep Regency, South Sulawesi. The problems faced are: (1) aspects of fish quality, (2) marketing, and (3) lack of knowledge on how to maintain the quality of fish trade and what types of fish are needed by customers. The solutions offered by the service proposing team are (1) introducing cold box technology for their merchandise, (2) introducing information technology to improve marketing, and (3) conducting technology transfers and training regarding cooler box technology and information technology to support marketing trading fish. The implementation method used in this community service activity uses a participatory approach involving all members of the partner group. The approach taken is in the form of observation, lecture, question and answer, discussion, and training practice with group partners to provide solutions to problems. The results achieved by this activity are that the mobile fish seller partners get provision of understanding and skills that can be used independently in order to improve their welfare, even though this service activity has been completed.